The Utilization of Shallot Skin Waste as an Alternative to Vegetable Pesticides in Karangrejo Village, Gumukmas District, Jember Regency - pandu hutama; Nurindah Niken Wulandari; Salsabila Herliana; Risya Firdaus; Mita Ramadhani; Muhammad Thohari; Eliza Christin Lilian; Donnavinska Wijaya; Nadya Farahgusti; Andreansyah Pratama; Radiaz Culture (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2022)
Karangrejo is one of the villages with excellent potential in the form of the agricultural sector, especially in the cultivation of rice and corn. Pests and diseases are the main problems in the cultivation of rice and corn in Karangrejo Village, Gumukmas District, Jember Regency which can hamper the cultivation process and can cause crop failure. Pest and disease control in Karangrejo Village is carried out by simple spraying of chemical pesticides. Spraying chemical pesticides can cause pests to become more resistant to chemical pesticides, so plant-based pesticides are needed. Shallot skin has the potential to be used as a vegetable pesticide because it contains acetogenin and flavonoid compounds. The purpose of this service activity is to improve the knowledge and skills of farmers in Karangrejo Village, Gumukmas District, Jember Regency in making onion peel vegetable pesticides to control pests and diseases in food crops. The implementation of activities through KKN-Collaborative is carried out by providing socialization and training on making onion peel vegetable pesticides. The results of community service are the development and application of botanical pesticides to help increase plant productivity.